Emotions and Construction of National Identities in Historical Education - Delfín Ortega-Sánchez; Joan Pagès Blanch; Carlos Pérez-González (MDPI AG, 2020)
In this study, the authors analyzed the relationship between emotions and the construction of identities, particularly national identity. We reviewed the current debate on the role of emotions and feelings in people's actions and in the configuration of their worldviews and practical actions. The world is witnessing a revival of ideologies that seemed to have been definitively banished from human thought and political action in the 20th century; however, it is being proved not only that they have survived and grown, but that they are also widely disseminated through networks and have come to shape the thinking of the many people who use them when deciding the future of their societies and how they want them to be governed. The growth of populism is based on emotions and on the most extremely nationalistic discourses. We analyzed, first of all, the influence of emotions on the perception of social reality and on the construction of historical and social knowledge. Next, we focused on the implications that emotions have had on the teaching of history and on the results of an international exploratory selection of particularly relevant research. Finally, as a conclusion, we suggest some ideas for the search of a balance that considers the weight of reason and emotion in the teaching and learning of history.